2019
DOI: 10.1155/2019/2815279
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence Genes inEnterococcus faeciumandEnterococcus faecalisfrom Humans and Retail Red Meat

Abstract: The emergence of antimicrobial-resistant and virulent enterococci is a major public health concern. While enterococci are commonly found in food of animal origin, the knowledge on their zoonotic potential is limited. The aim of this study was to determine and compare the antimicrobial susceptibility and virulence traits of Enterococcus faecalis and Enterococcus faecium isolates from human clinical specimens and retail red meat in Slovenia. A total of 242 isolates were investigated: 101 from humans (71 E. faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
5
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 74 publications
(106 reference statements)
10
45
5
6
Order By: Relevance
“…In this study, E. faecium and E. faecalis were observed in 15.3% and 20.2% of the processed pork meat products, while a previous study suggested that E. faecium and E. faecalis was detected in 11.3% and 69.5% of red meat [11]. In Argentinean artisanal dry fermented sausages, the most frequently isolated enterococci was E. faecium (56%), followed by E. faecalis (17%) and other species (E. durans, E. casseliflavus, and E. mundtii) [21].…”
Section: Contamination Of Enterococcus Sppcontrasting
confidence: 62%
See 2 more Smart Citations
“…In this study, E. faecium and E. faecalis were observed in 15.3% and 20.2% of the processed pork meat products, while a previous study suggested that E. faecium and E. faecalis was detected in 11.3% and 69.5% of red meat [11]. In Argentinean artisanal dry fermented sausages, the most frequently isolated enterococci was E. faecium (56%), followed by E. faecalis (17%) and other species (E. durans, E. casseliflavus, and E. mundtii) [21].…”
Section: Contamination Of Enterococcus Sppcontrasting
confidence: 62%
“…Interestingly, the prevalence of E. faecium in the total sample was 15.3% (Table 1), but E. faecium was isolated from 68.8% of the FP samples, which suggested that some of the common ingredients might be contaminated with E. faecium, or E. faecium might be cross-contaminated from processing environments, including water. Other enterococci, including E. avium, E. raffinose, E. casseliflavus, E. gallinarum, E. durans, were also isolated from processed pork meat products, which is supported by the previous study on the isolation of enterococci, i.e., Enterococcus spp., including E. hirae, E. casselifavus, E. durans, E. devriesei, E. gilvus, E. mundtii, and E. thailandicus, which were also isolated from beef and pork samples [11]. SRP and SSP contained a variety of ingredients including seasoning and fresh vegetables such as garlic, green onion and onions, and thus, different enterococci might originate from seasoning and raw vegetables.…”
Section: Contamination Of Enterococcus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported earlier, hyl was detected only in E. faecium [33]. Nevertheless, a few studies have reported the incidence of hyl in both species [29,[34][35][36][37][38][39]. Significant difference was observed in the VF score between species.…”
Section: Discussionmentioning
confidence: 54%
“…Nevertheless, the presence of virulence determinants in the clinical isolates might contribute to increased severity as they could be expressed under optimum conditions in vivo. Metadata of the previous studies on the detection of virulence genes of enterococci by multiplex/duplex/simplex PCR is depicted in Additional file 1: Table S1 [18,27,29,[33][34][35][36][37][38][39][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%